2019
DOI: 10.1038/s41467-019-12455-4
|View full text |Cite
|
Sign up to set email alerts
|

UHRF1 suppresses retrotransposons and cooperates with PRMT5 and PIWI proteins in male germ cells

Abstract: DNA methylation, repressive histone marks, and PIWI-interacting RNA (piRNA) are essential for the control of retrotransposon silencing in the mammalian germline. However, it remains unknown how these repressive epigenetic pathways crosstalk to ensure retrotransposon silencing in the male germline. Here, we show that UHRF1 is responsible for retrotransposon silencing and cooperates with repressive epigenetic pathways in male germ cells. Conditional loss of UHRF1 in postnatal germ cells causes DNA hypomethylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
68
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 62 publications
(64 reference statements)
5
68
1
Order By: Relevance
“…Uhrf1 has been shown to interact with PRMT5 (arginine methyltransferase) to catalyze the formation of H4R3me2s and H3R2me2s. These marks also act together with PIWI proteins to facilitate retrotransposon silencing in the germline [47]. We found that H1t-oligonucleosomes associate with Tdkrh, a known interacting protein partner with Uhrf1 and PIWI proteins, further supporting our observations of association of H1t with repressed-repeat element chromatin domains in pachytene spermatocytes.…”
Section: Mass Spectrometric Identification Of Proteins Associated Witsupporting
confidence: 88%
“…Uhrf1 has been shown to interact with PRMT5 (arginine methyltransferase) to catalyze the formation of H4R3me2s and H3R2me2s. These marks also act together with PIWI proteins to facilitate retrotransposon silencing in the germline [47]. We found that H1t-oligonucleosomes associate with Tdkrh, a known interacting protein partner with Uhrf1 and PIWI proteins, further supporting our observations of association of H1t with repressed-repeat element chromatin domains in pachytene spermatocytes.…”
Section: Mass Spectrometric Identification Of Proteins Associated Witsupporting
confidence: 88%
“…In addition, a recent study showed that the Ubiquitin-like, Containing PHD and RING finger Domains 1 (UHRF1) protein may interact with MIWI and MILI to deposit DNA methylation or to further recruit PRMT5 to methylate arginine of histones [ 64 ]. This study demonstrated the requirement of UHRF1 in histone and DNA methylation.…”
Section: The Function Of Piwi Proteins and Pirnas In Transposon Silenmentioning
confidence: 99%
“…Nevertheless, there is still progress to further dissect Piwi pathways in Drosophilid spermatogonia such as possible nuclear to cytoplasmic shuttling of PIWI during spermatogonia mitosis [ 85 ]. Overall though, there are much fewer studies discussing piRNA biogenesis in the Drosophila male germline [ 86 , 87 , 88 , 89 , 90 ] compared to the female germline, which we predict may also be the trend in mosquitoes if spermatogenesis development patterns are similar.…”
Section: Genome Transposon Composition and Germline Specificity Ofmentioning
confidence: 88%